Algorithm Analysis Of Definite Integration By Using Desk Check Method - Rini Nooraini (Jurnal Informatika dan Bisnis, 2013)
We usually experience difficulties when determining output of a pseudocode algorithm, especially inrepetition control structure or nested loop algorithm. They are usually complicated. We got difficulties toguess the logic or specifiy the output. For instance, what is the end result of the looping? Is it true orfalse? Where is the start and finish point of the looping? Where is the boundary of looping body? Shouldthe looping continue or stop? Did looping occure during a boolean result or condition is true? Did loopingoccure until condition is true? In addition to this, because of limitation human mind to remember or to dothe looping, we need some tools to analyze it. Based on the mentioned problems, author seek a design ormethod, easy way to analyze variables either input or output variables along with the algorithm logic in aalgorithm psuedocode. This is the author’s purpose of designing table, which is called desk check. In thiscase, function of the desk check is documenting the history of several changes from a number of analyzedvariables, either input or output variables along with logic by using table. The purpose of this article isanalyze the answer of Algorithm Design of Definite Integration by Using Flowchart Method, as well asverification of example problem candidate, namely definite integration